A comparative study on glocal commercial advertisement perceptions - British and French viewers' responses to Red Bull. Issue 4 (2018) - Bremser, Kerstin; Walter, Nadine; Goehlich, Véronique
This exploratory study analyses advertising viewers' perceptions using the same well-known person across different countries. Depending on their cultural background the interviewees associated very different feelings with the historical character shown in the cartoon. Additionally, the articulation and the style of the underlying music were perceived in different ways by both cultures. However, the results show that even though the commercial and the lyrics are differently understood and interpreted, the targeted marketing message is equally conveyed. The differences in perceptions observed are correlated with the Hofstede indexes for cross-cultural dimensions. This study is the first one to analyse perceptions about the same historical celebrity used in advertising among different countries and to correlate them with the Hofstede dimensions. It can thus give answers to the applicability of a certain type of advertising in different cultures, given that Hofstede dimensions are available for the selected countries.